Ontology and Rules for Characterization of Sensors and Actuators Devices in AADL Models - Sales, Diego; Koliver, Cristian; Becker, Leandro (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
This paper presents a set of ontologies to organize concepts, categories, properties, and relationships that are typically used by designers for characterizing sensing and actuation devices that compose a given system architecture (SA). From the characterization of such devices, modeling can be done using the Architecture Analysis and Design Language (AADL). AADL supports modeling and analysis of functional and nonfunctional properties to evaluate quality attributes from ontology models. The paper also proposes an AADL property set that can be applied to sensors and actuators (S&A), based on previous researches with ontologies applied to sensor networks. Specific characteristics are provided to describe systems' quality attributes. This aims to be used for analyzing the designed architecture, and also its probable future evolution.